AIDS Kaposi sarcoma-derived cells produce and respond to interleukin 6. - Miles, S A (1990)
Cell lines derived from Kaposi sarcoma lesions of patients with AIDS (AIDS-KS cells) produce several cytokines, including an endothelial cell growth factor, interleukin 1 beta, and basic fibroblast growth factor. Since exposure to human immunodeficiency virus increases interleukin 6 (IL-6) production in monocytes and endothelial cells produce IL-6, we examined IL-6 expression and response in AIDS-KS cell lines and IL-6 expression in AIDS Kaposi sarcoma tissue. The AIDS-KS cell lines (N521J and EKS3) secreted large amounts of immunoreactive and biologically active IL-6. We found both IL-6 and IL-6 receptor (IL-6-R) RNA by slot blot hybridization analysis of AIDS-KS cells. The IL-6-R was functional, as [3H]thymidine incorporation by AIDS-KS cells increased significantly after exposure to human recombinant IL-6 (hrIL-6) at greater than 10 units/ml. When AIDS-KS cells (EKS3) were exposed to IL-6 antisense oligonucleotide, cellular proliferation decreased by nearly two-thirds, with a corresponding decrease in the production of IL-6. The decrease from IL-6 antisense in AIDS-KS cell proliferation was reversed by the addition of hrIL-6. We confirmed that AIDS-KS cells produced IL-6 in vivo by preparing RNA and tissue sections from involved and uninvolved skin from a patient with AIDS Kaposi sarcoma. We detected immunoreactive IL-6 in the involved tumor areas and to a lesser extent in the surrounding normal epidermis. Slot blot hybridization showed a great excess of IL-6 and IL-6-R RNA in involved skin compared to uninvolved skin. These results show that both IL-6 and IL-6-R are produced by AIDS-KS cells and that IL-6 is required for optimal AIDS-KS cell proliferation, and they suggest that IL-6 is an autocrine growth factor for AIDS-KS cells.